To make the function easy to graph using transformations of its parent function, we can rewrite it in the form:
y = a√(bx - h) + k
Given function: y = 8x - 24 - √3 + 1
First, simplify the function:
y = 8x - 23 - √3
Now, we can rewrite the function in the desired form by factoring out a constant from the x term:
y = √1(8(x - 23/8)) - √3
The transformed function with the following transformations:
a = 1
b = 8
h = 23/8
k = -√3
Transformations of the graph:
- Vertical shift down by √3 units
- Horizontal compression by a factor of 1/b = 1/8
- Horizontal shift right by h units (23/8)
- No vertical stretch or reflection
By transforming the function in this way, it will be easier to graph using transformations of its parent function.
Rewrite the function to make it easy to graph using transformations of its parent function. Describe the transformations of the graph. y=8x−24−−−−−−√3+1
1 answer